Anthropogenic emission controls reduce summertime ozone–temperature sensitivity in the United States - S. Li; S. Li; S. Li; H. Wang; H. Wang; H. Wang; X. Lu; X. Lu; X. Lu (Atmospheric Chemistry and Physics)
Ozone–temperature sensitivity is widely used to infer the impact of future climate warming on ozone. However, trends in ozone–temperature sensitivity and possible drivers have remained unclear. Here, we show that the observed summertime surface ozone–temperature sensitivity, defined as the slope of the best-fit line of daily anomalies in ozone versus maximum temperature (mΔO3-ΔT<mtext>max</mtext><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="2b26318fdcdf37cc459f4cdc7fbc4ab5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2725-2025-ie00001.svg" width="54pt" height="12pt" src="acp-25-2725-2025-ie00001.png"/></svg:svg>), has decreased by 50 % during 1990–2021 in the continental United States (CONUS), with a mean decreasing rate of −0.57 ppbv K−1 per decade (p < 0.01) across 608 monitoring sites. We conduct high-resolution GEOS-Chem simulations in 1995–2017 to interpret the mΔO3-ΔT<mtext>max</mtext><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="ccd84c6bbf928489d36d9fe0d3fcb77e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2725-2025-ie00002.svg" width="54pt" height="12pt" src="acp-25-2725-2025-ie00002.png"/></svg:svg> trends and underlying mechanisms in the CONUS. The simulations identify the dominant role of anthropogenic nitrogen oxide (NOx) emission reduction in the observed mΔO3-ΔT<mtext>max</mtext><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="c7c5fa6f5246103ba9d87b2b4862d5ee"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2725-2025-ie00003.svg" width="54pt" height="12pt" src="acp-25-2725-2025-ie00003.png"/></svg:svg> decrease. We find that approximately 76 % of the simulated decline in mΔO3-ΔT<mtext>max</mtext><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="2cef9aff0fe141dea7dd6770760926af"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2725-2025-ie00004.svg" width="54pt" height="12pt" src="acp-25-2725-2025-ie00004.png"/></svg:svg> can be attributed to the temperature indirect effects arising from the shared collinearity of other meteorological effects (such as humidity, ventilation, and transport) on ozone. The remaining portion (24 %) is mostly due to the temperature direct effects, in particular four explicit temperature-dependent processes, including biogenic volatile organic compound (BVOC) emissions, soil NOx emissions, dry deposition, and thermal decomposition of peroxyacetyl nitrate (PAN). With reduced anthropogenic NOx emissions, the expected ozone enhancement from temperature-driven BVOC emissions, dry deposition, and PAN decomposition decreases, contributing to the decline in mΔO3-ΔT<mtext>max</mtext><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="cf260c790e0b69cd44471658a3f354d1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2725-2025-ie00005.svg" width="54pt" height="12pt" src="acp-25-2725-2025-ie00005.png"/></svg:svg>. However, soil NOx emissions increase mΔO3-ΔT<mtext>max</mtext><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="b5baa9bd598fa8dc1e15622b7eeaf83e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2725-2025-ie00006.svg" width="54pt" height="12pt" src="acp-25-2725-2025-ie00006.png"/></svg:svg> with anthropogenic NOx emission reduction, indicating an increasing role of soil NOx emissions in shaping the ozone–temperature sensitivity. As indicated by the decreased mΔO3-ΔT<mtext>max</mtext><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="54pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="2797e13ffe922030e00688dad7ce107e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-2725-2025-ie00007.svg" width="54pt" height="12pt" src="acp-25-2725-2025-ie00007.png"/></svg:svg>, model simulations estimate that reduced anthropogenic NOx emissions from 1995 to 2017 have lowered ozone enhancement from low to high temperatures by 6.8 ppbv averaged over the CONUS, significantly reducing the risk of extreme-ozone-pollution events under high temperatures. Our study illustrates the dependency of ozone–temperature sensitivity on anthropogenic emission levels, which should be considered in future ozone mitigation in a warmer climate.